Augmentative and Alternative Communication - Scoping Review / Unterstützte Kommunikation - Scoping Review - Kollmar Anja; Hohenstein Christiane; Sabatino Adriana; Gantschnig Brigitte (Sciendo, 2018)
The effective use of Augmentative and Alternative Communication is challenging, not only for persons with complex communication needs, but also for their significant others. There is a need, therefore, for interprofessional collaboration in order to effectively assess, provide, and evaluate services.